2014
DOI: 10.4236/ajps.2014.526417
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization and Application of the Essential Oils from Chenopodium ambrosioides and Philodendron bipinnatifidum in the Control of Diabrotica speciosa (Coleoptera: Chrysomelidae)

Abstract: The compositions of essential oils from Chenopodium ambrosioides L. and Philodendron bipinnatifidum Schott were determined, and their potential effects on the nutrition and mortality of Diabrotica speciosa were studied. The extraction of the oils was performed by hydrodistillation (2 h) using a modified Clevenger apparatus and the oils were subsequently subjected to analysis by gas chromatography/flame ionization detector (CG/FID) and gas chromatography/mass spectrometry (GC-MS). A completely randomized design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The principal constituents found were α-terpinene, pcymene and trans-ascaridole. The remaining components identified were found in percentages ≤0.5% (Santiago et al, 2014).…”
Section: Resultsmentioning
confidence: 97%
“…The principal constituents found were α-terpinene, pcymene and trans-ascaridole. The remaining components identified were found in percentages ≤0.5% (Santiago et al, 2014).…”
Section: Resultsmentioning
confidence: 97%
“…Bozin et al characterized Lamiaceae species and the antimicrobial and antioxidant activities of the oils of Ocimum basilicum L., Origanum vulgare L., and Thymus vulgaris L. [ 6 ], and the chemical constituents of four populations of Piper aduncum L. from Distrito Federal, Brazil [ 7 ], were identified. Many other essential oils have been characterized, namely, sweet lime ( Citrus limetta Risso) [ 8 ], Chenopodium ambrosioides , Philodendron bipinnatifidum [ 9 ], cinnamon oil, eucalyptus oil, lemongrass oil, peppermint oil, citronella oil, turpentine oil [ 10 ], citronella oil [ 11 ], Tithonia diversifolia (Hemsl.) A.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the composition of volatile oils from Philodendron plants are still scarce. Limonene and copaene have been found in some other species of this genus, while caryophyllene has been observed in all of those studied taxa with some different stereochemical orientations and concentrations (Viana, Andrade-Neto & Pouliquen, 2002;Bezerra et al, 2002;Ottobelli et al, 2011;Castellar et al, 2013;Santiago et al, 2014;Bacchus et al, 2015;Joffard et al, 2017). Germacrene has also been investigated by Silva et al (2016) for Philodendron maximum K. Krause, as well as by Joffard et al (2017) for…”
Section: Discussionmentioning
confidence: 94%
“…Alliance et al (2017) investigated the potential effect of essential oils from the root of Philodendron deflexum Poepp on larvae of Aedes aegypti Linnaeus and Anopheles albirtasis Lynch-Arribálzaga. Santiago et al (2014) described the insecticidal activity of essential oils from the roots of Philodendron bipinnatifidum Schott on Diabrotica speciose. Germar and Silva et al (2016) reported the antibacterial activity of the Philodendron goeldii essential oil G. M Barroso against Corynebacterium glutamicum.…”
Section: Introductionmentioning
confidence: 99%